Manajemen Sumber Daya Manusia Dalam Meningkatkan Kinerja Organisasi Panji Pelopor di Pondok Pesantren - Hushunud Diana; Rofikatul Maula (JUMPA : Jurnal Manajemen Pendidikan, 2022)
This study aims to measure the performance of the Panji Pelopor organization with various trainings to serve as a support in providing insight and to improve the organizational performance of Panji Pelopor Pondok Pesantren Nurul Jadid. Training is carried out as one of the most important references in the organization in order to realize the performance of human resources produced in a quality and qualified organization. This research uses descriptive qualitative research methods and phenomenological designs, and with the target object in the interview process with several related parties, Head of HumPro (Humas & Protocol) who oversees the Pioneer Panji Organization, Pioneer Panji Trustees, Head of Panji Pelopor Boys & Girls Section, Staff, Management and Members of the Panji Pelopor Organization. In the research obtained by researchers as a form of supporting the performance of human resources in the Panji Pioneer organization, namely, through various trainings including Administrative Training, Protocol Training, Public Speaking Training.